Improving Competitiveness of Islamic Banking Through Human Resources (SDI) Development Strategy - Susanto, Hanafi Hadi (University of Darusssalam Gontor, 2019)
This paper aimes to analyse the good strategy in improving the human resource that should be used by the banking institutions to be better compared to others. This paper based on primary data from the book, journal and online database. The result of the study shows that one way and strategy to develop human resources in banking is by improving their knowledge, abilities, attitudes and so on. Also, good strategy can provide an overview of the main actions and decision patterns chosen to realize the goals of the organization and a company institution and in order for development to be carried out properly, a human resource development program must first be established. And with that, the quality (superior) Human Resouces will be able to provide more service and trust compared to others.